Post-practicum concerns among TESL trainee teachers: a case study / Muhammad Luthfi Mohaini - Mohaini, Muhammad Luthfi (2015)
This study investigated the concerns and experiences of trainee teachers regarding teaching practicum. This paper also intended to draw the stakeholders’ (university supervisors, school mentors and the faculty) attention to the underlying reasons given by TESL trainee teachers about their concerns regarding teaching practicum in order to integrate areas of concern into future management and development of teacher education program. A total of 15 trainee teachers were purposely selected where they had to maintain a reflective journal throughout their practicum to document their teaching concerns and confidence to teach. This study was qualitative in nature where case study was conducted to get in depth data. Their reflective journals were analyzed based on Wellington’s (2000) Constant Comparative Method. Next, structured interview questions were constructed in relation to the themes found and sent via email to the respondents’ supervisors to gain insights and verification on the themes of concern. The findings showed that thirteen derived concerns were identified and placed into four main themes: (a) classroom management and discipline (b) classroom teaching; (c) student learning and (d) personal adjustments. The most highlighted concern was classroom management and discipline where every respondent had problems controlling the students almost every day. The implications underlined in the study were towards being aware of the teaching practicum concerns and providing better experiences in teaching practicum. It is hoped that, the information highlighted in this study can help the stakeholders (university supervisors, school mentors and the faculty) to determine future actions needed in teacher education programs to better prepare teacher candidates.